Surgery With or Without Postoperative Radiation Therapy for Early-stage External Auditory Canal Squamous Cell Carcinoma: A Meta-analysis. Issue 9 (October 2017) - Oya, Ryohei; Takenaka, Yukinori; Takemura, Kazuya; Ashida, Naoki; Shimizu, Kotaro; Kitamura, Takahiro; Yamamoto, Yoshifumi; Uno, Atsuhiko
Abstract : Objective: External auditory canal squamous cell carcinoma (EACSCC) is a rare disease with no standard treatment supported by high-level evidence. The aim of this study was to investigate EACSCC prognoses according to treatment modality and thus determine the optimal intervention for early-stage disease. Data Sources: PubMed, Scopus, and Ichushi-Web searches of the English and Japanese-language literature published between January 1, 2006 and December 31, 2016 were performed using the key words "external auditory canal cancer" and "temporal bone cancer." Study Selection: Articles related to EACSCC that include the 5-year overall survival rate or individual patient data for histological types, follow-up periods, and final outcomes were enrolled. Data Extraction: Sex, age, Moody's modified Pittsburgh stage, type of treatment modality, type of operation, follow-up period, and 5-year survival rates were extracted. Data Synthesis: Twenty articles were used for the aggregate meta-analysis using a random-effects model, and 18 articles that reported 99 patients with early-stage EACSCC were used for the individual patient data meta-analysis. Conclusion: The 5-year overall survival rate of early-stage EACSCC was 77%. Postoperative radiation therapy (PORT) was performed in 45% of stage I patients and 68% of stage II patients. Survival analysis of all patients showed no differences between the surgery-only and PORT groups; however, PORT exhibited a better prognosis than surgery alone among patients with stage I disease ( p  = 0.003, log-rank test). This result indicated that PORT can be the standard therapy for stages I and II EACSCC.